2018
DOI: 10.3390/en11020315
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Performance Assessment of a Novel Micro-CCHP System Based on a Low Temperature PEMFC Power Unit and a Half-Effect Li/Br Absorption Chiller

Abstract: The aim of this work has been to evaluate the energetic feasibility and the performances of a novel residential micro-Combined Cooling, Heating and Power (CCHP) system, based on low temperature proton exchange membrane fuel cell (PEMFC) power unit and half effect lithium bromide absorption chiller. This integrated system has been designed to produce both electric, thermal and cooling power by recovering heat from the fuel cell power unit cooling system. The analysis has been conducted by using numerical simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 40 publications
1
22
1
Order By: Relevance
“…As a source of cold it is proposed to use absorption refrigeration machine. [13][14][15][16][17] The operational principle of an absorption refrigeration machine is based on certain properties of the refrigerant and absorbent, which provide heat removal, cooling and maintaining the required temperature conditions. At present, the industry widely uses absorption refrigeration machines to produce cold in an area of positive temperatures for various technological needs.…”
Section: Methodsmentioning
confidence: 99%
“…As a source of cold it is proposed to use absorption refrigeration machine. [13][14][15][16][17] The operational principle of an absorption refrigeration machine is based on certain properties of the refrigerant and absorbent, which provide heat removal, cooling and maintaining the required temperature conditions. At present, the industry widely uses absorption refrigeration machines to produce cold in an area of positive temperatures for various technological needs.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, the author concluded that for generator temperatures higher than In the literature, there have been many reports about theoretical and experimental works on singleand double-effect absorption systems: However, the literature about absorption half-effect systems is scarce. Cozzolino [14] described a residential micro-Combined Cooling, Heating and Power (CCHP) system, including a low-temperature Proton Exchange Membrane Fuel Cell (PEMFC) power unit and a half-effect lithium bromide absorption chiller. The author carried out numerical simulations in order to demonstrate the energetic feasibility and performance of this configuration.…”
Section: Introductionmentioning
confidence: 99%
“…This condition is attributed to the particularly scarce peak-load regulation power (hydropower and condensing unit) in these areas compared with the numerous combined heat and power (CHP) units. The CHP units have considerable environmental and financial benefits when compared to conventional energy generation [3][4][5][6][7]. However, a CHP unit is subject to a heat load-based constraint, which causes its power output to be high in the heating season and limits the access space of wind power in the grid [8].…”
Section: Introductionmentioning
confidence: 99%